Claims of Rights to Urban Space: A Comparison of Ghettoised and Non-ghettoised Muslim Residents of Kolkata - Saha, Ahala (National Geographical Journal of India, 2022)
Most research pursuits on people following Islam and inhabiting cities in India have taken the researcher to urban slums. These clearly are not mere coincidences but outcomes of very deep-rooted and persistent deprivations, so much so that these economic deprivations today have become characteristic of Muslims in Indian cities. Urban poor Muslims in India mostly live in areas that are poverty stricken and dirt filled city spaces. Also, they are ghettos. However, there are poor Muslims in Indian cities who live outside ghettos, in a mix with others. This study argues that those who live within ghettos have stronger voices as compared to those who do not. Ghettos therefore are those city spaces that ensure greater freedom and lesser hesitations. However, this is not to undermine the fact that ghettos are spaces of deprivation and evidences of denial of the right to the city.